فاعلية الذكاء الاصطناعي في نمذجة بيئة التعلم وانعكاساته على أداء بعض المهارات الأساسية بدرس التربية الرياضية لدى تلاميذ المرحلة الإعدادية ذوي صعوبات التعلم الحركي - درويش، محمد سالم حسين (جامعة أسيوط - كلية التربية الرياضية, 2023)
استهدف البحث الحالي التعرف على فاعلية الذكاء الاصطناعي في نمذجة بيئة التعلم وانعكاساته على أداء بَعْض المهارات الأساسية بدرس التربية الرياضية لدى تلاميذ المرحلة الإعدادية ذَوِي صُعوبات التعلم الحركي، استخدم الباحث المنهج شبه التجريبي ذُو التصميم التجريبي لمجموعتين إحداهما تجريبية والأخرى ضابطة، باتباع القياسات القبلية البعدية نظرًا لملاءمته لطبيعة البحث، كما تُمثَّل مُجتمع البحث في تلاميذ الصف الأول بالمرحلة الإعدادية بمدرسة عزيز أباظة الرسمية للغات، والتابعة لإدارة شرق مدينة نصر بمحافظة القاهرة، والبالغ عدده (۱۱۰) تلميذًا لِلْعَام الدراسي ۲۰۲۲ / ۲۰۲۳م، كذلك قام الباحث باختيار عينة البحث بالطريقة العمدية من تلاميذ الصف الأول بالمرحلة الإعدادية بمدرسة عزيز أباظة الرسمية للغات، التابعة لإدارة شرق مَدِينَة نَصْر - بمحافظة القاهرة للعام الدراسي ٢٠٢٢ / ۲۰۲۳م، والبالغ قوامها (۳۰) تلميذًا مِن إجمالي مُجتمع البحث، بنسبة مئوية (۲۷,۲۷۳%) من المجتمع الكلى للبحث، تم تقسيمهم إلى مجموعتين إحداهما تجريبيَّة، والْأُخْرِى ضَابِطة، بواقع تصنيفي (١٥) تلميذا لكل مجموعة، كما قام الباحث باختيار مجموعتين من التلاميذ مِن مُجتمع البحث، وخارج العيّنة الأساسية، إحداهما (مجموعة مُميزة) والمتمثلة في التلاميذ المشاركين بفريق كرة القدم بالمدرسة والأخرى (مجموعة غَيْر مُميزة)، والمتمثلة في التلاميذ غير المشاركين بفريق كرة القدم بالمدرسة، بواقع تصنيفي (١٥) تلميذًا لِكُلِّ مَجْمُوعة، وَذَلِكَ بِهَدف إجراء المعاملات العلمية للمتغيّرات "قيد البحث"، ولم يُواجه الباحث أي حالة من حالات الإعاقة البدنية أو السمعية أو البصرية التي يُمكن استبعادها عن اختيار عينة البحث، كذلك تم استبعاد (٦٠) تلميذا لم تنطبق عليهم الخصائص السلوكية لصعوبات التعلم الحركي، واستخدم الباحث برنامج الحزم الإحصائية للعلوم الاجتماعية لإجراء المعالجات الإحصائية للبيانات الأساسية داخل هذا البحث باستخدام: Statistical Package for Social Science SPSS وقد توصل الباحث إلى الاستنتاجات التالية: فاعلية المنهاج التعليمي / والأنشطة التعليمية بالبرنامج التعليمي المقترح باستخدام النمذجة الاصطناعية لبيئة التعلم على أداء تلاميذ المجموعة التجريبية للمهارات الأساسية بكرة القدم "قيد البحث"، وفقًا لنسب التطور التي ظهرت، تفوق تلاميذ المجموعة التجريبية على تلاميذ المجموعة الضابطة في الأداء الفني (مُسْتَوَى التَّعلم) للمهارات الأساسية بكرة القدم "قيد البحث". كما يُوصي الباحث بالآتي: توفير بنية تحتية الإلكترونية لوحدة مركزية على مستوى الجامعة يتم من خلالها تدريب الطلاب وأعضاء هيئة التدريس على تطبيقات الذكاء الاصطناعي ونظم المعلومات والاتصالات في ضَوْء التَّحَول الرقمي، التخطيط المستقبلي لدمج التكنولوجيا الحديثة في بنية المدارس وتطبيق أحدث نُظُم الذكاء الاصطناعي فِي دَعْم عَمَليتي التعليم والتعلم، تدريب معلمي التربية الرياضية على استخدام نظم التعلم الذكية وتوظيفها بشكل يُساعد على تعليم المهارات الأساسية بدرس التربية الرياضية لدى تلاميذ المرحلة الإعدادية ذوي صعوبات التعلم الحركي. The current research aimed to identify the effectiveness of artificial intelligence in modeling the learning environment and its implications for the performance of some skills. In studying physical education among preparatory school students with motor learning difficulties, the researcher used the A quasi-experimental approach with an experimental design for two groups, one experimental and the other control, following tribal measurements dimensionality due to its suitability Due to the nature of the research, it also represents the research community on first-grade students in the preparatory stage at Aziz Abaza Public School. Languages, which is affiliated with the East Nasr City Administration in Cairo Governorate, and its number is (110) students for the academic year 2022/2023 AD, as well as Therefore, the researcher chose the research sample intentionally from students The first grade of the preparatory stage at Aziz Abaza Official Language School, affiliated with the East Nasr City Administration - Governorate Cairo School for the academic year 2022/2023 AD, which consists of (30) students out of the total research community, with a percentage of (27.2 73%) of the total research community, they were divided into Two groups, one experimental and the other control, with 15 students for each group. The researcher also chose Two groups of students from the research community, outside the main sample, one of them (a distinct group), represented by the students The participants in the football team at one school and the other (an undistinguished group), which is represented by students who do not participate in the school football team, with a classification of (15) students for each group, and that is by The goal is to conduct scientific treatments of the variables “under research,” and the researcher did not encounter any case of physical disability or Audio or visual that can be excluded from sample selection During the research, (60) students who did not meet the behavioral characteristics of motor learning difficulties were excluded, and the For the SPSS researcher to conduct the statistical processing of the basic data within this Search using: Statistical Package for Social Science SPSS. The researcher reached the following conclusions: The effectiveness of the educational curriculum/educational activities in the proposed educational program using artificial modeling to The learning environment affects the performance of the students of the experimental group for basic football skills “under research”, according to the rates of development She appeared. The students of the experimental group outperformed the students of the control group in the technical performance (learning level) of your basic skills. "Under investigation". The researcher also recommends the following: Providing electronic infrastructure for a central unit at the university level through which students and faculty members are trained. Teaching on applications of artificial intelligence and information and communications systems in light of digital transformation. Future planning to integrate modern technology into the structure of schools and apply the latest artificial intelligence systems to support my work Teaching and learning. Training physical education teachers to use smart learning systems and employ them in a way that helps teach basic skills By studying physical education among preparatory school students with motor learning difficulties.
Keywords: التربية الرياضية -- التعلم الرقمي -- المهارات الأساسية -- طلبة المرحلة الإعدادية -- صعوبات التعلم